2012
DOI: 10.1021/jm300388h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of a Series of 2-Aryl-4-Amino-5-(3′,4′,5′-trimethoxybenzoyl)Thiazoles as Novel Anticancer Agents

Abstract: A new series of tubulin polymerization inhibitors based on the 2-aryl/heteroaryl-4-amino-5-(3′,4′,5′-trimethoxybenzoyl)thiazole scaffold was synthesized and evaluated for growth inhibition activity on a panel of cancer cell lines, cell cycle effects, and in vivo potency. Structure–activity relationships were elucidated with various substitutions at the 2-position of the thiazole skeleton. Hydrophobic moieties, such as phenyl and 3-thienyl, were well tolerated at this position, and variation of the phenyl subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…24,25 It is based on the principal that light is scattered by microtubules to an extent that is proportional to the concentration of the microtubule polymer. Compounds that interact with tubulin will alter the polymerization of tubulin, and this can be detected using a spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 It is based on the principal that light is scattered by microtubules to an extent that is proportional to the concentration of the microtubule polymer. Compounds that interact with tubulin will alter the polymerization of tubulin, and this can be detected using a spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…website and curated sixteen important medicinal chemistry papers carefully for analysis of the structure–activity relationship (SAR) and the binding pose of these ligands (Chart S1). From the year 2004–2012, Silvestri group reported a series of colchicine‐site inhibitors with arylthioindole skeleton, and recently their attentions were shifted to the replacement of the indole ring with thiazole . Kremmidiotis group depicted a class of tubulin polymerization inhibitors derived from the benzofuran scaffold, in which compound 95 ( BNC105 , Figure ) had been investigated under the clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the alternation of the parent nucleus could circumvent tumor resistance . The compounds with mono‐aromatic ring system (thiazole or thiophene) might possess much of variation on alternative binding pose ; thus, this needed to be discussed carefully in the design process of novel CSIs. Thirdly, the SAR studies on the linker of a series of arylthioindole compounds revealed that A region tended toward the rigid moiety, such as ketone or amide, while the methylene can be tolerated .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations